2003
DOI: 10.1002/adfm.200304312
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Fly Ash Cenosphere to Hollow Microspheres with Zeolite/Mullite Composite Shells

Abstract: A seed‐induced in‐situ hydrothermal conversion technique is proposed to prepare novel hollow microspheres with zeolite/mullite composite shells from fly ash cenosphere (FAC), a solid waste with a hollow structure from coal power stations. Two groups of hollow microspheres were prepared, one with zeolite FAU/mullite composite shells and the other with zeolite LTA/mullite composite shells. The FAC in this study plays dual roles as both the template cores and the aluminosilicate nutrition contributor. The final p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…Furthermore, fly ash cenosphere (FAC, an aluminosilicate-rich waste from power plants) is used as a hollow spherical template and nutriments to prepare hollow zeolitic microspheres with cancrinite zeolite shell through in situ transformation of FAC in vapor phase. [675][676][677] Xiong et al 678 employed spherical mesoporous DAM-1 or SBA-15 as a silicon source and substrate to prepare hollow ZSM-5 spheres by using a combination of pulsed laser deposition (PLD) and VPT processes. The size of ZSM-5 crystals in the shell can be easily adjusted by changing the crystallization time or PLD coating thickness.…”
Section: Hierarchically Micro-macroporous Structuresmentioning
confidence: 99%
“…Furthermore, fly ash cenosphere (FAC, an aluminosilicate-rich waste from power plants) is used as a hollow spherical template and nutriments to prepare hollow zeolitic microspheres with cancrinite zeolite shell through in situ transformation of FAC in vapor phase. [675][676][677] Xiong et al 678 employed spherical mesoporous DAM-1 or SBA-15 as a silicon source and substrate to prepare hollow ZSM-5 spheres by using a combination of pulsed laser deposition (PLD) and VPT processes. The size of ZSM-5 crystals in the shell can be easily adjusted by changing the crystallization time or PLD coating thickness.…”
Section: Hierarchically Micro-macroporous Structuresmentioning
confidence: 99%
“…There are several spheres have been used as the template such as polystyrene microsphere [9], mesoporous silica spheres [10], and fly ash cenosphere, etc. [11]. Meanwhile, based on this core-shell method several groups have synthesized hollow zeolitic microcapsule [8] [12].…”
mentioning
confidence: 99%
“…The temperature condition of MTBE adsorption process is specially designed in view of both S/FAC composite large-scale application in environmental field in the future and the inherently characteristics of MTBE. Three typical solution temperatures (10,20, 30 • C), which are below the boiling point of MTBE 55.2 • C, were selected to perform the study. As the temperature variation is not big, no obvious effect of temperature was found on the adsorption of MTBE by S/FAC and silicalite-1 even the process should be exothermic.…”
Section: Adsorption Of Mtbe By S/fac Compositementioning
confidence: 99%
“…It has been reported that nanosized zeolite as seeds could be fabricated on various supports for the preparation of hierarchical micro/meso/macroporous zeolite composite [9][10][11]. Fly ash cenosphere (FAC), an aluminosilicate-rich waste produced in coal-firing power plants, could be a kind of feasible support for zeolite composite, based on its economical low cost; excellent chemical/physical stability; and non-toxic release of its component [10,11]. Recently, the nanozeolite composite zeolite/FAC with a hierarchical porous structure has been successfully prepared by us through a seed-induced hydrothermal treatment method [10,11].…”
Section: Introductionmentioning
confidence: 99%